2016
DOI: 10.1055/s-0036-1571296
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Receptor Modulation for the Treatment of Nonalcoholic Fatty Liver Disease

Abstract: Nuclear receptors (NRs) are ligand-activated transcriptional regulators of several key metabolic processes including hepatic lipid and glucose metabolism, bile acid homeostasis, and energy expenditure as well as inflammation, fibrosis, and cellular proliferation in the liver. Dysregulation of these processes contributes to the pathogenesis and progression of nonalcoholic fatty liver disease (NAFLD). This places NRs at the forefront of novel therapeutic approaches for NAFLD. Some NRs are already pharmacological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
10

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 228 publications
(280 reference statements)
0
79
0
10
Order By: Relevance
“…New selective PPAR modulators have been developed to overcome the limitations of the current fibrates. These include the dual PPARα/γ agonist aleglitazar and the dual PPARα/δ agonist elafibranor (GFT505) 80, 81. These dual agonists can improve insulin resistance and fasting hypertriglycemia and low‐density lipoprotein (LDL) cholesterol levels as well as liver enzymes in obese and insulin‐resistant males and in rodent NASH and fibrosis models.…”
Section: Nuclear Receptors As Therapeutic Targetsmentioning
confidence: 99%
“…New selective PPAR modulators have been developed to overcome the limitations of the current fibrates. These include the dual PPARα/γ agonist aleglitazar and the dual PPARα/δ agonist elafibranor (GFT505) 80, 81. These dual agonists can improve insulin resistance and fasting hypertriglycemia and low‐density lipoprotein (LDL) cholesterol levels as well as liver enzymes in obese and insulin‐resistant males and in rodent NASH and fibrosis models.…”
Section: Nuclear Receptors As Therapeutic Targetsmentioning
confidence: 99%
“…2). Так, активация FXR в энтероцитах под-вздошной кишки после активного захвата ими желчных кислот приводит к продукции фактора роста фибробла-стов 15 (FGF15, ортолог у человека -FGF19) [14], репрес-сирующего синтез желчных кислот, способствующего снижению уровня de novo липогенеза в печени и опо-средованно стимулирующего β-окисление жирных кис-лот в митохондриях [15,16].…”
Section: биология фарнезоидного рецептораunclassified
“…Агонисты FXR, такие как его естественные лиганды (холевая и хенодезоксихолевая кислоты), синтетически модифицированные желчные кислоты (6α-этилхеноде-зоксихолевая (обетихолевая) кислота, INT-747), а также синтетические нестероидные молекулы (GW4064 и WAY-362450) продемонстрировали эффективность при тера-пии НАЖБП и НАСГ в нескольких доклинических иссле-дованиях на лабораторных животных [12,16,17].…”
Section: применение агонистов и антагонистов Fxr в лечении нажбп/насгunclassified
See 1 more Smart Citation
“…NHRs may bind a variety of ligands, however, two NHRs that can act in the liver have been shown to bind specific PC species. PPARα has a well established role as a regulator of fatty acid oxidation, lipid transport and gluconeogenesis [55] and it is the target of therapeutics [56]. The Semenkovich lab used tandem mass spectrometry to identify endogenous ligands for PPARα in the mouse liver and found that a specific species of phosphatidylcholine (16:0/18:1 GPC) was associated with the active transcription factor [57].…”
Section: Mechanisms Of Low-pc Action On Lipogenesis: Pc Itself or Dowmentioning
confidence: 99%